1978
DOI: 10.1212/wnl.28.8.847
|View full text |Cite
|
Sign up to set email alerts
|

Penicillamine‐induced myasthenia gravis associated with antibodies to acetylcholine receptor

Abstract: A woman with rheumatoid arthritis was treated with penicillamine and developed myasthenia gravis. This drug-induced disease was associated with characteristic autoantibodies to acetycholine receptor. After discontinuing the drug, her symptoms improved and the antibody titers fell. Penicillamine is now being used much more frequently in the treatment of rheumatoid arthritis and it is likely that this complication will become more prevalent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0
2

Year Published

1979
1979
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(13 citation statements)
references
References 0 publications
1
10
0
2
Order By: Relevance
“…Previous reports of penicillamine-induced MG have been limited to Wilson's disease (20,26) and rheumatoid arthritis (1 [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Unpublished observations (34) have noted two cases of penicillamine-induced MG in patients with scleroderma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports of penicillamine-induced MG have been limited to Wilson's disease (20,26) and rheumatoid arthritis (1 [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Unpublished observations (34) have noted two cases of penicillamine-induced MG in patients with scleroderma.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous side effects may develop in patients receiving penicillamine (10,13), including autoimmune disorders such as systemic lupus erythematosus (14), pemphigus (19, Goodpasture's syndrome (16), and polymyositis (17). Recently several patients who developed unequivocal my asthenia gravis (MG) have been reported (18)(19)(20)(21)(22)(23)(24)(25). The majority of patients with penicillamine-induced MG had RA, but 2 patients with Wilson's disease have also been reported (20,26).…”
mentioning
confidence: 99%
“…Recently, it has been suggested that gold-related pulmonary fibrosis, a rare complication of chrysotherapy, might also have an autoimmune pathogenesis (Smith and Ball, 1980). Penicillamine seems to be frequently associated with autoimmune reactions: many types of "autoimmune diseases," including systemic lupus erythematosus, myasthenia gravis, Goodpasture's syndrome, and dermatomyositis, and variety of autoantibodies, such as anti-acety1cholin receptor, and antimitochondrial and antinuclear antibodies have been reported to develop in patients treated with this drug (O'Brien, 1980;Russel and Lindstrom, 1978;Kirby et ai., 1979;Zilko et ai., 1977).…”
Section: Gold-induced Autoimmune Reactions Timo P Alosuo and Felix MImentioning
confidence: 99%
“…The rate of fall of anti-AChR was 50% in 45 to 60 days. Attempts to reproduce this condition in experimental animals by treatment with penicillamine has so far been unsuccessful (see Russell and Lindstrom, 1978), but the temporary nature of the myasthenia gravis suggests that the drug has a direct reversible effect on the immune system. AChR levels from a number of patients undergoing various forms of treatment.…”
Section: The Antigenic Stimulus In Mgmentioning
confidence: 99%